2003
DOI: 10.1046/j.1365-2672.2003.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7, Listeria monocytogenes 4b and Yersinia enterocolitica O3 in different yogurt and kefir combinations as prefermentation contaminant

Abstract: Aims:To compare microbiological safety of yogurt, kefir and different combinations of yogurt and kefir samples by using three foodborne pathogenic strains (Escherichia coli O157:H7, Listeria monocytogenes 4b and Yersinia enterocolitica O3) as indicators. Methods and Results: Fresh yogurt and kefir drinks were added to pasteurized milk at a 5% rate either separately or together, and then incubated at different temperatures (43°C for yogurt and 30°C for kefir), depending on appropriate growth temperature of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 20 publications
5
33
0
3
Order By: Relevance
“…The results support the hypothesis that fermented dairy products, especially natural kefir and probiotic yogurt, may have F. nucleatum inhibitory characteristics. Their potent antimicrobial and antitumor properties have also reported in previous studies [7,13,22].…”
Section: Disc Diffusion-zone Inhibition Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The results support the hypothesis that fermented dairy products, especially natural kefir and probiotic yogurt, may have F. nucleatum inhibitory characteristics. Their potent antimicrobial and antitumor properties have also reported in previous studies [7,13,22].…”
Section: Disc Diffusion-zone Inhibition Resultssupporting
confidence: 67%
“…Kefir has antimicrobial properties against some bacteria groups due to its competitive flora and unique metabolites. It is reported that kefir inhibits the bacterial growth of S. aureus [10,11], K. pneumoniae, E. coli [12], Listeria monocytogenes, Salmonella typhimurium, S. enteriditis, S. flexneri, Yersinia enterocolitica [9,13], and E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial properties of kefir coculture, as has also previously been suggested for dairy products (26), may be attributed either to its ability to produce lactic acid and therefore cause a drastic reduction in pH or to the production of antimicrobial compounds by certain strains existing in its natural microbial flora (55,57,60). Our results show that the sugar consumption, production of lactic acid, and therefore reduction of pH observed in unsalted rennet cheese due to the action of indigenous lactic acid bacteria that survive pasteurization (61) are inadequate to provide the products lacking starter cultures the preservation properties gained by kefir.…”
Section: Discussionmentioning
confidence: 73%
“…[38]. Antibiotic activity of both kefir and purified AK (50 mg·mL −1 ) has been evaluated [8] using both the disk diffusion method and susceptibility tests against some well known pathogenic bacteria (S. pyogenes, S. salivarius, S. aureus, P. aeruginosa, S. tiphymurium, E. coli, L. monocytogenes, and C. albicans).…”
Section: On Microorganismsmentioning
confidence: 99%